2017
DOI: 10.1007/s10753-017-0602-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in the Suppression of Immune Responses in Peripheral Blood Mononuclear Cells Exposed to Combustible Tobacco Product Preparation

Abstract: Cigarette smoking is a major risk factor for several human diseases. Chronic inflammation, resulting from increased oxidative stress, has been suggested as a mechanism that contributes to the increased susceptibility of smokers to cancer and microbial infections. We have previously shown that whole-smoke conditioned medium (WS-CM) and total particulate matter (TPM) prepared from Kentucky 3R4F reference cigarettes [collectively called as combustible tobacco product preparations (TPPs)] potently suppressed agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Genes in DNA repair pathways are vital in protecting DNA from multiple types of damage initiated by tobacco's chemical carcinogens (Hoeijmakers, ). Genetic variations, such as SNPs of DNA repair genes, modify DNA repair efficiency by changing protein function and therefore increase the risk for various cancers (de Boer, ; Xi et al, ), such as chronic pulmonary disease and lung malignancy (Arimilli, Schmidt, Damratoski, & Prasad, ; Kheradmand et al, ). Among DNA repair genes, the TDG gene was identified as the first mismatch‐specific enzyme playing a key role in recognizing and correcting a variety of damaged and/or mismatched nucleotides (Cortazar et al, ; Da & Yu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Genes in DNA repair pathways are vital in protecting DNA from multiple types of damage initiated by tobacco's chemical carcinogens (Hoeijmakers, ). Genetic variations, such as SNPs of DNA repair genes, modify DNA repair efficiency by changing protein function and therefore increase the risk for various cancers (de Boer, ; Xi et al, ), such as chronic pulmonary disease and lung malignancy (Arimilli, Schmidt, Damratoski, & Prasad, ; Kheradmand et al, ). Among DNA repair genes, the TDG gene was identified as the first mismatch‐specific enzyme playing a key role in recognizing and correcting a variety of damaged and/or mismatched nucleotides (Cortazar et al, ; Da & Yu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of alveolar macrophages is increased in BAL of smokers, a vast body of evidence suggests that these cells are functionally impaired [ 189 , 190 , 191 , 192 , 193 , 194 ]. Specifically, the ability to release pro-inflammatory cytokines (e.g., Il-1, IL-5, Il-6, IL-8, IL-12, TNF-α, IP-10, MCP-1, MIP-1α, and VEGF) seems to be substantially reduced following CSE and oxidative stress appears to be implied [ 195 , 196 ]. This explains, at least in part, why AMs from smokers elaborate a blunted inflammatory response after LPS stimulation, which results in increased susceptibility to infections [ 193 , 197 , 198 , 199 ].…”
Section: Effects Of Cigarette Smoke Exposure On the Immune Systemmentioning
confidence: 99%
“…Most findings in the literature are consistent regarding the association of obesity and higher levels of IL-6 and CRP, corroborating our results. For smoking, several authors have also found an association with inflammatory biomarkers [43, 44], but this has not been as consistent as for obesity [45, 46].…”
Section: Discussionmentioning
confidence: 99%